PERTAHANAN MARITIM INDONESIA MELALUI PENGUATAN ALUTSISTA MARITIM BERBASIS TEKNOLOGI DRONE LAUT DALAM MENCEGAH ANCAMAN MARITIM DI KAWASAN INDO-PASIFIK TAHUN 2015-2020 - Adam Muhammad Firdaus (2022)
This study aims to describe maritime defense and strengthening of maritime drone defense equipment such as Indonesian AUV, ROV, and UMV in the Indo-Pacific Region in 2015-2020. The theory used is the maritime environment, maritime security, maritime defense, and maritime defense equipment. The method used in this research is descriptive analytical qualitative using primary data sources and secondary data. The final result of this research Based on the formulation of the problem and the line of thought above, Indonesian defense based on the use of marine drones can prevent maritime security threats in the Indo-Pacific region. In this case, it can be seen that Indonesia already has marine drones that are used in order to maintain the defense and security of the maritime area. And with the implementation of Indonesia's defense using marine drones, Indonesia's maritime forces will be more active in maintaining maritime security in the Indo-Pacific and be respected both regionally and globally. Keywords: maritime defense equipment, marine drones, Indo-Pacific, maritime security, maritime threats